Ekstrak Antosianin Dari Ubi Ungu (Ipomoea Batatas L.) Sebagai Pewarna Alami Pada Pemeriksaan Soil Transmitted Helminths (STH) Metode Natif (Direct Slide) - Subakir Salnus; Dzikra Arwie; Zulfian Armah (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2021)
Helminthiasis is a worm infestation caused by several different species of intestinal parasitic worms. This group of worms belongs to the category of Soil Transmitted Helminth (STH) because the process of developing eggs or larvae of these species requires soil to develop into an infective form. The simplest method of examining intestinal nematode worm eggs is the Native Method using 2% Eosin reagent in observing various elements of the examination on the preparations/preparations. Eosin itself has properties that are not easily biodegradable, and generates hazardous waste (toxic) and flammable so that alternative coloring is needed that is more environmentally friendly. Purple sweet potato has a high content of anthocyanin pigments and is more stable than the pigments of strawberries, red cabbage, perilla and other plants. Thus, purple sweet potato has been considered a good source of anthocyanins. This study aims to determine the use of anthocyanin extract from purple sweet potato as a natural dye substitute for eosin dye in the identification of STH in the native method. Parameters observed in the preparations were the quality of visual field contrast, color absorption on the surface of the parasite, and the level of clarity of the appearance of the parasite. The results showed that the use of anthocyanin extract from purple sweet potato at a concentration of 80% could color the eggs of STH worms which were found in positive samples of Ascaris lumbricoides seen in fertile (fertilized eggs) and infertile (unfertilized eggs). Therefore, the anthocyanin extract obtained from purple sweet potato has potential as an alternative dye to replace eosin.